Local Wisdom of Medicinal Plants in Petak Puti Village, Central Kalimantan - Herianto Herianto; Demitra Demitra; Triyadi A; Gimson Luhan; Yosep Yosep (PT FORMOSA CENDEKIA GLOBAL, 2026)
This research aims to Identify each type of plant that has the potential to be used as medicine in Petak Puti Village; Describe the use and processing methods of plants that have the potential to be used as medicine. The research uses a qualitative method with a descriptive research design. Observation, to obtain information about the initial stages of the research, was conducted to seek information about traditional medicine that utilizes medicinal plants in Petak Puti Village. The informant selection technique used the purposive sampling method, carried out by selecting informants for certain considerations, in this case, the person who is considered to know the most about the situation in the village. The determination of informants purposively is assumed that the selected informants represent a homogeneous community, consisting of main informants (key informants) to be interviewed such as the village head, traditional leaders and immigrants who are married to village residents. While the basic informants are village members, traditional members and residents outside the village who have knowledge about the village. The local wisdom of plant species is very significant in the views and perceptions of the community in meeting basic human needs. The Dayak Ngaju Katingan community is highly dependent on natural resources to meet various daily needs. Most of the community's income comes from forest plant products. The diversity of plant species can provide food products for the community, produce various types of plants for consumption as a supplement for the Dayak community and generate alternative sources of income, such as used as food, medicines, fermentation, tonics, cosmetics, building materials and other materials, which can provide important nutrients and vitamins as supplements for the community, and can provide a buffer in times of food shortages. In addition, existing plant species have great potential to be developed and cultivated into new plants and provide genetic resources and conduct selection.